Analisis Faktor Risiko Kematian Ibu di Kabupaten Jember Menggunakan Cox Proportional Hazard - Roydatul Jamila; Mohamat Fatekurohman; Dian Anggraeni (ESTIMASI: Journal of Statistics and Its Application, 2023)
Maternal mortality is the death of a woman who is pregnant, giving birth and childbirth to the pregnancy or its handler. Maternal mortality in East Java Province still quite high with the highest number of deaths in 2021 is Jember Regency. The purpose of this paper is to determine risk factors that cause death in an effort to reduce the number of maternal deaths. Method used for the analysis of risk factors for maternal mortality is survival analysis with the Cox Proportional Hazard model. Survival analysis purpose to assess the relationship of predictor variables to survival time to determine maternal survival. Cox Proportional Hazard model is one of the models in survival analysis that is often used. Selection of the best model for Cox Proportional Hazard is carried out to determine the factors that have a significant effect. The best model is done by selecting the smallest AIC value backwards. Parameter significance test on the best model was carried out simultaneously and partially. Results obtained for maternal mortality factors in Jember Regency are anemia status and parity.